Translational Effect of Provider-Focused, Multi-State, Multi-Clinic Asthma Care Quality Improvement Program on Patient-Level Health Care Costs. (March 2021) - Rojanasarot, Sirikan; Carlson, Angeline M.; St. Peter, Wendy L.; Karaca-Mandic, Pinar; Wolfson, Julian; Schommer, Jon C.
Introduction/Objectives: Enhancing Care for Patients with Asthma (ECPA), a year-long provider-focused, multi-state, multi-clinic quality improvement program, decreased avoidable utilizations among patients with asthma, but its effects on health care expenditures were not determined. This study examined the translational and sustainable effects of improved care through ECPA on individual-level total health care costs due to asthma. Methods: We conducted a retrospective pretest-posttest quasi-experimental study in which attributed 1683 patients in a 12-month pre-ECPA implementation period served as their own control. We constructed the total annual asthma-related health care costs per patient occurred during pre-ECPA implementation, ECPA implementation, and post-ECPA completion. We used 3-level generalized linear mixed models (GLMMs) to estimate the ECPA effect on the annual health care costs and account for correlation between the repeated outcome measures for each patient and nested clinic. All costs were adjusted for inflation to 2014 U.S. dollars, the last year of program observation. Results: Total asthma-related health care costs among the 1683 included patients decreased from an average of 7033 to 3237 per person-year (pre-ECPA implementation vs implementation). Using the cost data from the 12-month pre-ECPA implementation period as a reference, GLMMs found that the ECPA implementation was associated with a reduction in total annual asthma-related health care costs by 56.4% (95% CI −60.7%, −51.8%). During the 12-months after ECPA completion period, health care costs were also found to be significantly lower, experiencing a 57.3% reduction. Conclusions: The economic benefits of ECPA provide a justification to adopt this quality improvement initiative to more primary care clinics at a national level.